Pemberdayaan Kampung KB Sekip Jaya Pada Program Dapur Sehat Atasi Stunting - Budiarta, Kustoro; Hidayat, Ahmad; Lubis, Nurul Wardani; Hasyim, Diana (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Kampung KB Sekip Jaya is prepared as a pilot Kampung KB for stunting prevention. Through the Dapur Sehat Atasi Stunting (DASHAT) programme, Kampung KB Sekip Jaya was implementing a government programme in the form of 100 days to overcome stunting by providing additional nutritionally balanced food to children who are identified as stunted. Together with the Kampung KB Activity Groups (BKB, BKR, BKL and UPPKA), the P3A and P2KB Office of Deli Serdang Regency, the Sekip Village Government and other community groups, the DASHAT programme was implemented as an effort to prevent stunting and build quality families. In its implementation, the DASHAT programme in Kampung KB Sekip Jaya faces various problems, namely: 1) DASHAT management was still conventional so that the 100-day programme to overcome stunting was not supported by the DASHAT work programme, 2) Community empowerment has not been maximised, especially in involving nutritionists and culinary experts, 3) Community empowerment, especially the Activity Group Kampung KB, was not in accordance with its function so that the target of the DASHAT programme was still limited, 4) Human resources involved in the DASHAT programme have low knowledge and understanding of DASHAT management and stunting prevention. The solutions offered through this activity were: 1) training and practice of DASHAT management, 2) training and practice of food production made from local raw materials for each Activity Group Kampung KB as a superior product that sells well.  The method used was partner assistance through training and practice of DASHAT management, training and production practices so that partners have a productive business unit that can be used as a source of financing for the family and for the Kampung KB Sekip Jaya. The results of the activity show that the participants' insights have increased, especially in preparing food menus for 100 days to overcome stunting, the availability of work programs in DASHAT management, the practice of processed marine fish production and the superior product of Kampung KB Sekip Jaya in the form of fish biscuits as a product that will be produced by the UPPKA group as the spearhead of the productive economy in Kampyng KB Sekip Jaya.